AKT controls protein synthesis and oxidative metabolism via combined mTORC1 and FOXO1 signalling to govern muscle physiology. Issue 1 (9th November 2021) - Jaiswal, Natasha; Gavin, Matthew; Loro, Emanuele; Sostre‐Colón, Jaimarie; Roberson, Paul A.; Uehara, Kahealani; Rivera‐Fuentes, Nicole; Neinast, Michael; Arany, Zoltan; Kimball, Scot R.; Khurana, Tejvir S.; Titchenell, Paul M.
Abstract: Background: Skeletomuscular diseases result in significant muscle loss and decreased performance, paralleled by a loss in mitochondrial and oxidative capacity. Insulin and insulin‐like growth factor‐1 (IGF‐1) are two potent anabolic hormones that activate a host of signalling intermediates including the serine/threonine kinase AKT to influence skeletal muscle physiology. Defective AKT signalling is associated with muscle pathology, including cachexia, sarcopenia, and disuse; however, the mechanistic underpinnings remain unresolved. Methods: To elucidate the role of AKT signalling in muscle mass and physiology, we generated both congenital and inducible mouse models of skeletal muscle‐specific AKT deficiency. To understand the downstream mechanisms mediating AKT's effects on muscle biology, we generated mice lacking AKT1/2 and FOXO1 (M‐AKTFOXO1TKO and M‐indAKTFOXO1TKO) to inhibit downstream FOXO1 signalling, AKT1/2 and TSC1 (M‐AKTTSCTKO and M‐indAKTTSCTKO) to activate mTORC1, and AKT1/2, FOXO1, and TSC1 (M‐QKO and M‐indQKO) to simultaneously activate mTORC1 and inhibit FOXO1 in AKT‐deficient skeletal muscle. Muscle proteostasis and physiology were assessed using multiple assays including metabolic labelling, mitochondrial function, fibre typing, ex vivo physiology, and exercise performance. Results: Here, we show that genetic ablation of skeletal muscle AKT signalling resulted in decreased muscle mass and a loss of oxidative metabolism and muscle performance. Specifically, deletion of muscle AKT activity during development or in adult mice resulted in a significant reduction in muscle growth by 30–40% ( P   < 0.0001; n  = 12–20) and 15% ( P  < 0.01 and P  < 0.0001; n  = 20–30), respectively. Interestingly, this reduction in muscle mass was primarily due to an ~40% reduction in protein synthesis in both M‐AKTDKO and M‐indAKTDKO muscles ( P < 0.05 and P  < 0.01; n  = 12–20) without significant changes in proteolysis or autophagy. Moreover, a significant reduction in oxidative capacity was observed in both M‐AKTDKO ( P  < 0.05, P  < 0.01 and P  < 0.001; n  = 5–12) and M‐indAKTDKO ( P  < 0.05 and P  < 0.01; n  = 4). Mechanistically, activation and inhibition of mTORC1/FOXO1, respectively, but neither alone, were sufficient to restore protein synthesis, muscle oxidative capacity, and muscle function in the absence of AKT in vivo . In a mouse model of disuse‐induced muscle loss, simultaneous activation of mTORC1 and inhibition of FOXO1 preserved muscle mass following immobilization (~5–10% reduction in casted M‐indFOXO1TSCDKO muscles vs. ~30–40% casted M‐indControl muscles, P  < 0.05 and P  < 0.0001; n  = 8–16). Conclusions: Collectively, this study provides novel insights into the AKT‐dependent mechanisms that underlie muscle protein homeostasis, function, and metabolism in both normal physiology and disuse‐induced muscle wasting.